2021
DOI: 10.1080/23735082.2020.1871062
|View full text |Cite
|
Sign up to set email alerts
|

Which conditions facilitate the effectiveness of large-group learning activities? A systematic review of research in higher education

Abstract: Large-group activities has increased in higher education since year 2000. Research focused on the possibility to have positive effects on students' learning, regardless the number of students by identifying facilitating factors. Hence, the achievement of learning results is used as a criterion of effectiveness. This review summarizes the findings of research studies on conditions that determine the effectiveness of large-group learning activities in higher education contexts published from 1996 to 2016. The PR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…The solutions to the problems were discussed and misconceptions were identified. Feedback is a known affordance of face-to-face settings and with the help of trained peer learners can be implemented in large classes (Jerez et al, 2021). In the online system, limited feedback was available to the students while working on a problem in the form of correct/incorrect indicators, but the full feedback was not immediate.…”
Section: Discussionmentioning
confidence: 99%
“…The solutions to the problems were discussed and misconceptions were identified. Feedback is a known affordance of face-to-face settings and with the help of trained peer learners can be implemented in large classes (Jerez et al, 2021). In the online system, limited feedback was available to the students while working on a problem in the form of correct/incorrect indicators, but the full feedback was not immediate.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, lecturers should incorporate active learning strategies such as group work, peer instruction, and problem-based learning. Active teaching and learning methods can be defined as strategies that promote the participation of students in a way that encourages them to perform tasks and activities towards their learning process, instead of the traditional passive experience (Jerez et al, 2021). Furthermore, to ensure that teaching and learning are more active in large classes, lecturers can include brainstorming, short writing activities, class discussion, formative quizzes, debates, and student presentations (Mulryan-Kyne 2010).…”
Section: Incorporate Active Learning Methodsmentioning
confidence: 99%
“…This can be in the form of online discussion forums, online classes using Zoom or Microsoft teams platforms, video conferencing, and automated assessment grading systems. The use of online teaching resources is considered as an important aid that help solving the challenges of large-group activities, through the involvement of other learners and the readily available electronic resources inside and outside the classroom (Jerez et al, 2021). Kerr (2011) concurs and recommends that lecturers need to keep abreast of advances in pedagogical approaches and new technologies to better their large class teaching experience.…”
Section: Use Technology In Teachingmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, many studies in the literature explored the predictors of academic success in web-based courses. A review of 78 studies on the conditions that determine the effectiveness of large-group learning activities in higher education showed the following: (1) student-teacher and student-student interaction, (2) implementation of active learning strategies, (3) classroom management, (4) students' motivation and commitment, and (5) the use of online teaching resources (Jerez, Orsini, Ortiz & Hasbun, 2021). Another study with one hundred forty students in 19 online courses showed that both environmental factors, instructors' autonomy-supportive interaction and learning environments using constructivist-based pedagogy predicted students' autonomous self-regulated motivation which in turn predicted students' self-reported engagement, achievement, and satisfaction.…”
Section: Introductionmentioning
confidence: 99%